Long term outcomes and complications of reno‐portal anastomosis in liver transplantation: results from a propensity score‐based outcome analysis. (31st August 2021) - D'Amico, Giuseppe; Matsushima, Hajime; Del Prete, Luca; Diago Uso, Teresa; Armanyous, Sherif R.; Hashimoto, Koji; Eghtesad, Bijan; Fujiki, Masato; Aucejo, Federico; Sasaki, Kazunari; Kwon, Choon Hyuck David; Simioni, Andrea; et al.
Summary: Diffuse splanchnic vein thrombosis (DSVT) remains a serious challenge in liver transplantation (LT). Reno‐portal anastomosis (RPA) has previously been reported as a valid option for management of patients with DSVT during LT. The aim of this study was to evaluate post‐transplant renal function and surgical outcomes of patients with DSVT who underwent RPA during LT. Between January 2005 and December 2017, 1270 patients underwent LT at our institution, including 16 with DSVT managed with RPA (RPA group). We compared renal function and surgical outcomes in these patients to outcomes in 48 propensity score (PS)‐matched patients without thrombosis (control group), using a 1:3 matching model. The two groups had similar rates of postoperative portal vein thrombosis (PVT), renal dysfunction as measured by estimated glomerular filtration rate (eGFR), and overall postoperative complications (Clavien grade III), although the RPA group had a higher incidence of postoperative upper gastrointestinal (GI) bleeding (31.3% vs 4.2%; P = 0.009) that had no clinical consequence. There were no significant differences in five‐year graft and patient survival rates between the groups ( P = 0.133 and P = 0.166, respectively). RPA is an established technique in the management of patients with DSVT during LT, with comparable outcomes to patients without thrombosis. Our report is the first to demonstrate similar surgical outcomes, including long‐term renal function, in LT recipients with or without RPA. Abstract : Long term patient survival, graft survival and renal function in liver recipients with severe portal vein thrombosis treated with renoportal anastomoisis compared to patients without thrombosis that underwent conventional portal vein anastomosis.